2008
DOI: 10.1111/j.1479-828x.2007.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive use and associations with intimate partner violence among a population‐based sample of New Zealand women

Abstract: Aim:  To outline the use of contraception among a representative sample of New Zealand women, and explore associations with intimate partner violence (IPV), and contraception and condom use. Methods:  Face‐to‐face interviews were conducted with a random sample of 2790 women who had ever had sexual intercourse, aged 18–64 years old in two regions (urban and rural) in New Zealand. Analyses were conducted using logistic regression and Wald χ2 tests. Results:  Almost all women had used contraception at some point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
52
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 12 publications
10
52
2
1
Order By: Relevance
“…While this finding contrasts with many previous studies, including those in Jordan [6,8], it adds to a growing body of international literature that demonstrates a positive association between IPV and female contraception use [13,14]. Additionally, among previous studies that disaggregated types of IPV, there was evidence from sub-Saharan Africa that sexual violence was positively associated with contraception use [13].…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…While this finding contrasts with many previous studies, including those in Jordan [6,8], it adds to a growing body of international literature that demonstrates a positive association between IPV and female contraception use [13,14]. Additionally, among previous studies that disaggregated types of IPV, there was evidence from sub-Saharan Africa that sexual violence was positively associated with contraception use [13].…”
Section: Discussioncontrasting
confidence: 73%
“…Although no significant association [2,14]. Women who reported ever experiencing severe physical violence had on average significantly lower odds of currently using contraception (OR = 0.34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inconsistent use of contraceptive may express the great difficulty involved in negotiating contraception for women in violent relationships. Fanslow et al 36 have pointed out that a partner's refusal to use contraception may be an indicator of violence in the context of relationships between couples, which is reiterated by Brazilian studies 17,36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Fanslow et al conducted a large study of over 2,300 women who had ever been pregnant and found that experiencing violence during pregnancy resulted in a lower proportion of women reporting wanting the pregnancy (28% vs. 55%), and a higher proportion of women reporting later access to prenatal care, smoking, and/or alcohol use during the pregnancy (67% vs. 22% and 31% vs. 20%, respectively). 11 Although both the prevalence of unintended pregnancy and its consequences are well documented, the literature is very limited with respect to environmental factors such as community and neighborhood-level violence and unintended pregnancy rates, particularly in urban areas. To our knowledge, only one study has explored the role of violence in the community as it relates to unintended pregnancy.…”
Section: Introductionmentioning
confidence: 99%